1996
DOI: 10.2172/239309
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of maternal radionuclide burdens to prenatal radiation doses

Abstract: Although t h e listing that follows represents t h e majority of documents cited in NRC publications. it is not intended to b e exhaustive.Referenced documents available for inspection and copying for a fee from t h e NRC Public Document Room include NRC correspondence and internal NRC memoranda: NRC bulletins, circulars, information notices, inspection and investigation notices; licensee event reports: vendor reports and correspondence; Cornmission papers; and applicant and licensee documents and corresponden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…These were derived from the specific activity of 131 I present in raw milk in southern Bavaria, assuming a consumption rate for dairy produce of 120 kg per year. Foetal doses due to ingested radionuclides were derived on the basis of an elaborate model which takes into account morphology and growth during pregnancy, and appropriate biokinetic models for different stages of gestation [16].…”
Section: Estimated Embryonic/foetal Dosementioning
confidence: 99%
See 2 more Smart Citations
“…These were derived from the specific activity of 131 I present in raw milk in southern Bavaria, assuming a consumption rate for dairy produce of 120 kg per year. Foetal doses due to ingested radionuclides were derived on the basis of an elaborate model which takes into account morphology and growth during pregnancy, and appropriate biokinetic models for different stages of gestation [16].…”
Section: Estimated Embryonic/foetal Dosementioning
confidence: 99%
“…Figure 3 shows the rate of intake for 131 I, as roughly estimated from the specific activity of 131 I present in raw milk in southern Bavaria and a consumption rate of 120 kg per year of dairy produce. The foetal doses due to ingestion of 134 Cs, 137 Cs, and 131 I were calculated from the gestation-stage-dependent dose conversion factors listed by Sikov and Hui [16]. The total contributions due to ingestion are brought together in Table 1.…”
Section: Estimated Embryonic/foetal Dosementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the First International Congress of Radiology (1925) concentrated efforts first on measurements and then protection. The International X-Ray Unit Committee (IXRUC) was born [later to become the International Commission on Radiological Units (ICRU) in 19501; the International Commission on Radiological Protection (ICRP) was conceived, but not yet born (Taylor 1989).…”
Section: Development Of Reliable Methods Of Measuring Exposure and Dosementioning
confidence: 99%
“…Placental transfer is small (ICRP 2002;NCRP 1998;Sikov and Hui 1996) indicating that the levels proposed in Table 1 are adequate to provide protection for the fetus. This is consistent with Fisher et al (1994) who concluded that the "age of the subject was not an important factor in assessing the consequences factor of airborne uranium" and that the extant standards were adequate to protect children and the fetus (Fisher et al 1994).…”
Section: Applicability To Child and Fetusmentioning
confidence: 99%